Analisis Kebutuhan Pengembangan Penuntun Praktikum Mikrobiologi Mahasiswa Pendidikan Biologi Institut Turatea Indonesia Jeneponto - Anita H; Satriani (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
This study aimed to analyze the needs for developing microbiology practicum guides for biology education students at the Turatea Indonesia Jeneponto Institute. It also aimed to determine the appropriate forms and approaches for these guides. The data was collected using a validated questionnaire. The questionnaires were distributed to 30 students majoring in biology education and eight lecturers from the biology education study program at the Turatea Indonesia Jeneponto Institute. The results indicated a need for the development of the Microbiology Practicum Guide based on the science process skills currently used at the Indonesian Turatea Institute, Jeneponto. The proposed format for the Microbiology Practicum Guide is a video tutorial. In the Microbiology Practicum Guide at the Indonesian Turatea Institute, Jeneponto, the KPS approach is still regarded as relevant.